Growth kinetics of a Helianthus annuus and a Salvia fruticosa suspension cell line: Shake flask cultivations with online monitoring system. Issue 6 (8th May 2013) - Geipel, Katja; Socher, Maria Lisa; Haas, Christiane; Bley, Thomas; Steingroewer, Juliane
<x xml:space="preserve">Abstract</x> Plants produce a variety of secondary metabolites to defend themselves against herbivores or to attract pollinating insects. Plant cell biotechnology offers excellent opportunities in order to use such secondary plant metabolites to produce goods with consistent quality and quantity throughout the year, and therefore to act independently from biotic and abiotic environmental factors. This article presents results of an extensive study of plant cell in vitro cultivation in a modern shake flask system with noninvasive online respiration activity monitoring unit. Comprehensive screening experiments confirm the successful transfer of a model culture (sunflower suspension) into the shake flask monitoring device and the suitability of this respiration activity monitoring unit as qualified tool for screening of plant in vitro cultures (sunflower and sage suspension). The authors demonstrate deviations between online and offline data due to varying water evaporation from different culture flask types. The influence of evaporation on growth‐specific parameters thereby rises with increasing cultivation time. Furthermore, possibilities to minimize the impact of evaporation, either by adjusting the inlet air moisture or by measuring the evaporation in combination with an appropriate correction of the measured growth values are shown.